Psychiatry essentials : - Kolevzon, Alex (Hanley & Belfus, Inc., 2002)
Comprehensive review of clinical psychiatry written from a student's perspective. Each topic is divided into three sections: 'The Basics,' 'Essential Features,' and 'Depth and Detail,' corresponding to a different point in the rotation. DNLM: Mental Disorders--Examination Questions.